Method for preparing high-compaction lithium iron phosphate based on organic additive and application thereof

CN121376947BActive Publication Date: 2026-11-03GUIZHOU PHOSPHATE KAIRUI TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511752634.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-26
Publication Date
2026-11-03
Estimated Expiration
2045-11-26

AI Technical Summary

Technical Problem

In existing technologies, it is difficult to synergistically improve the compaction density and electrochemical performance of lithium iron phosphate materials using the single-sintering method, while the two-sintering method has a long process flow and high cost, which limits the large-scale industrial application of lithium iron phosphate materials.

Method used

By using specific organic additives to mix and wet grind materials during a single sintering process, a uniform amorphous carbon coating layer and metal element doping are generated. Through in-situ carbon coating and lattice optimization, the high compaction density and excellent electrochemical performance are simultaneously improved.

Benefits of technology

While simplifying the process, it significantly improves the compaction density and electrochemical performance of lithium iron phosphate, especially exhibiting excellent capacity and conductivity at high rates, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121376947B_ABST
    Figure CN121376947B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium battery positive electrode materials, and specifically discloses a method for preparing high-compaction lithium iron phosphate based on an organic additive and application thereof, which comprises the following steps: S1, mixing a lithium source, an iron source, a phosphorus source, a carbon source and an organic additive in pure water to obtain a mixture; S2, wet grinding the mixture to obtain a slurry; S3, spray drying the slurry to obtain a lithium iron phosphate precursor; and S4, sintering the lithium iron phosphate precursor under an inert gas protection atmosphere to obtain a lithium iron phosphate positive electrode material. The method adopts one-time sintering solid-phase method, introduces the organic additive as a single precursor through sand grinding, the organic part of the organic additive is decomposed to form a uniform conductive carbon layer in the sintering process, and metal elements in the organic additive are doped into the lithium iron phosphate crystal lattice in situ; the method does not need hydrothermal reaction and particle compounding, directly prepares the lithium iron phosphate positive electrode material with high-compaction density and high discharge specific capacity through the synergistic effect of doping and coating, and the process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery cathode material technology, specifically to a method for preparing high-pressure lithium iron phosphate based on organic additives and its application. Background Technology

[0002] Lithium-ion batteries, as a new generation of green energy, possess advantages such as high voltage, high energy density, long lifespan, and portability, playing a crucial role in mobile devices, public transportation, aerospace, and other fields. Among these, cathode materials, as a vital component of lithium-ion batteries, influence their research and development. Lithium iron phosphate (LFP), as a cathode material for lithium-ion batteries, boasts abundant raw material sources, low cost, good thermal stability, high voltage platform, long cycle life, non-toxicity, and no oxygen evolution under abuse conditions. It can solve safety issues that lithium cobalt oxide and other existing cathode materials cannot address, making it the preferred cathode material for power and energy storage lithium-ion batteries. However, its relatively low energy density has always been a key factor restricting its widespread application. Energy density is closely related to the material's compaction density; therefore, developing high-compaction-density LFP materials has become a current research hotspot. Currently, the industry generally aims for a powder compaction density of 2.6 g / cm³. 3 The above lithium iron phosphate materials are defined as high-density lithium iron phosphate.

[0003] In existing technologies, lithium iron phosphate materials are typically prepared using hydrothermal methods or high-temperature solid-state sintering. The hydrothermal method uses water as a solvent, where the powder is dissolved and recrystallized. For example, patent CN116002648A discloses a high-pressure, low-temperature lithium iron phosphate cathode material, its preparation method, and its application. This method involves adding citrate and organic solvents during the hydrothermal process to generate nanoscale primary particles, and then adding a binder for spray pyrolysis to generate large-particle lithium iron phosphate with high lithium-ion mobility and excellent low-temperature performance. These large particles are then mixed with the small-particle lithium iron phosphate generated by the hydrothermal process, improving the overall low-temperature performance and compaction density of the material. Sintering methods include ferrous oxalate primary sintering, iron phosphate primary sintering, and iron phosphate secondary sintering. Traditional single-stage sintering methods do not require carbothermic reduction reactions. They directly use ferrous oxalate or ferric phosphate as precursors and complete carbon coating and crystal structure formation through a single high-temperature sintering. Although single-stage sintering is simple and low-cost, it is often difficult to optimize the uniformity of carbon coating, the regularity of particle morphology, and the integrity of crystal structure during the sintering process. This leads to a significant contradiction between the compaction density and electrochemical performance (such as rate capacity and cycle life), resulting in limited performance improvement. Two-stage sintering methods require two-stage sintering. For example, patent CN109244462A, a method for preparing high-conductivity lithium iron phosphate materials, discloses a method of coating the surface of lithium iron phosphate with a layer of organic carbon source derived from sugar decomposition through a single sintering, followed by a second sintering to coat the lithium iron phosphate / carbon surface with a layer of high-temperature pyrolysis carbon with a high degree of graphitization. Patent CN102225752B, a method for rapidly preparing LiFePO4 cathode materials, discloses a method of grinding lithium source, organic additives, iron source, and phosphate source uniformly and then sintering in a double crucible. The secondary sintering method improves the overall performance of materials to a certain extent through complex process steps, but it inevitably brings problems such as long process flow, high energy consumption, and increased production costs, which are not conducive to large-scale industrial application.

[0004] Therefore, how to simultaneously improve the compaction density and electrochemical performance of lithium iron phosphate materials through an efficient and low-cost modification method while retaining the simplicity of the single sintering process has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] One of the objectives of this invention is to provide a method for preparing high-compact lithium iron phosphate based on organic additives, which solves the problems of uneven compaction in the first sintering and the long and costly second sintering process in the prior art, and achieves a dual improvement in the compaction density and electrochemical performance of lithium iron phosphate.

[0006] The second objective of this invention is to provide a method for preparing high-pressure lithium iron phosphate based on organic additives, and its application in battery manufacturing.

[0007] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a method for preparing high-pressure lithium iron phosphate based on organic additives, comprising the following steps: S1. A lithium source, an iron source, a phosphorus source, a carbon source, and an organic additive are mixed in pure water to obtain a mixture; wherein the organic additive is one or more of the following: iron citrate, titanium citrate, tetrabutyl titanate, aluminum citrate, methyl titanate, and tetraethyl titanate. S2. The mixture is wet-milled to obtain a slurry with a solid particle size D50 of 0.2 to 0.6 μm; S3. Spray dry the slurry to obtain lithium iron phosphate precursor; S4. The lithium iron phosphate precursor is sintered under an inert gas protective atmosphere to obtain lithium iron phosphate cathode material.

[0008] Furthermore, in S1, the amount of the organic additive added is 0.5-5% of the mass of the iron source.

[0009] Furthermore, in S1, the carbon source is one or more of sucrose, glucose, starch, PEG, ascorbic acid, and cellulose.

[0010] Furthermore, in S1, the amount of carbon source added is 5% to 15% of the mass of the iron source.

[0011] Further, in S1, the phosphorus source is one or more of phosphoric acid, monoammonium phosphate, diammonium phosphate, and ferric phosphate; the iron source is one or more of ferrous oxalate, ferric phosphate, iron oxide, ferric pyrophosphate, ferrous dihydrogen phosphate, and ferrous phosphate; the lithium source is one or more of lithium carbonate and lithium hydroxide; and the elemental molar ratio of the lithium source, iron source, and phosphorus source is Li:Fe:P = 1~1.05:1:1~1.07.

[0012] Furthermore, in S1, the solid content of the mixture is 30% to 60%.

[0013] Furthermore, in S4, the inert gas is one or both of argon and nitrogen.

[0014] Furthermore, in S4, the sintering temperature is 700–810°C, and the sintering time is 6–14 h.

[0015] Secondly, this invention provides an application of a method for preparing high-pressure lithium iron phosphate based on organic additives in battery manufacturing.

[0016] Compared with existing technologies, the present invention has the following beneficial effects: This invention, by introducing specific organic additives, ingeniously achieves multiple synergistic effects in a simple one-time sintering process, thereby preparing high-pressure lithium iron phosphate. Specifically, the organic additives have the following key functions: 1. In-situ carbon coating and particle morphology control: Organic additives can decompose or carbonize during high-temperature sintering, generating a uniform amorphous carbon coating layer in situ. This coating layer not only effectively blocks direct contact between precursor particles, inhibiting excessive particle growth and agglomeration, thereby refining the grain size of the final product and obtaining smaller, more uniformly distributed secondary spherical particles; this coating layer also improves the overall electronic conductivity of the material, compensating for the insufficient intrinsic conductivity of lithium iron phosphate, reducing side reactions at the electrode interface, enhancing structural stability, and thus improving electrochemical performance.

[0017] 2. Metal element doping and lattice optimization: During sintering, organic additives (especially those containing metal elements such as titanium citrate) can introduce metal elements (such as titanium, iron, and aluminum) into the lithium iron phosphate lattice, forming effective element doping. This doping helps stabilize the crystal structure, expand lithium-ion diffusion channels, and reduce the activation energy of lithium-ion transport. Therefore, while increasing the material's compaction density, it significantly ensures and improves the material's electrochemical performance, especially at high rates.

[0018] 3. The amount of element doping in the organic additive in this invention can be adjusted according to the mass fraction. An appropriate amount of organic additive can not only provide enough carbon source to form a uniform coating layer, but also introduce an appropriate amount of doping elements. Too little may lead to uneven carbon coating or insufficient doping, while too much may introduce impurities or affect the purity of the crystal.

[0019] 4. The wet milling process controls the particle size D50 to be between 0.2 and 0.6 μm, ensuring the uniformity of the precursor particles. This is crucial for forming a dense structure and uniform carbon coating during subsequent sintering. Optimization of sintering temperature and time ensures sufficient crystallization of lithium iron phosphate, formation of the carbon layer, and effective doping of metal elements, while avoiding excessive particle growth. Through synergistic optimization of these parameters, this invention successfully achieves a balance between high compaction density and excellent electrochemical performance.

[0020] 5. The preparation method features simple synthesis process and uniform mixing, which can realize large-scale production on the production line.

[0021] Through the synergistic effect of carbon coating and metal element doping, this invention successfully overcomes the contradiction in the synergistic optimization of compaction density and electrochemical performance in the traditional one-time sintering method, and achieves simultaneous improvement of the performance of both. Attached Figure Description

[0022] Figure 1This is a SEM image of the lithium iron phosphate cathode material prepared in Example 1 of the present invention. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] According to a first aspect of the present invention, a method for preparing high-pressure lithium iron phosphate based on organic additives is provided.

[0025] Example 1: A method for preparing high-pressure lithium iron phosphate based on organic additives, comprising the following steps: (1) Lithium carbonate, iron phosphate, titanium citrate and glucose with a Li:Fe:P molar ratio of 1.02:1:1.05 were mixed. The amount of glucose added was 10% of the mass of iron phosphate and the amount of titanium citrate was 1% of the mass of iron phosphate. Water was added at the same time to control the solid content to 50% and the mixture was mixed evenly. Then, a sand mill was used for wet grinding to make a mixed slurry with a solid particle size D50 of 0.3μm.

[0026] (2) The above mixed slurry is spray-dried. The inlet temperature of the spray dryer is 200℃ and the outlet temperature is 100℃. After the temperature is qualified, the precursor is obtained by spray granulation.

[0027] (3) The precursor obtained after spray drying is sintered under nitrogen. The sintering furnace environment requires that the oxygen content in the nitrogen is less than 20 ppm and that it be isolated from the outside air. The total sintering time is 12 hours. The precursor is heated to 750℃ for 6 hours and then held at this temperature for 6 hours. The sintered material is then subjected to airflow pulverization in a constant temperature and humidity chamber. The particle size D50 is controlled to be 0.8-1.4 micrometers, D90 is less than 5 micrometers, and D100 is less than 12 micrometers to obtain lithium iron phosphate cathode material. Figure 1 This is a SEM image of the lithium iron phosphate cathode material.

[0028] Example 2: A method for preparing high-pressure lithium iron phosphate based on organic additives The only difference from Example 1 is that the sintering temperature in step (3) is 770°C.

[0029] Example 3: A method for preparing high-pressure lithium iron phosphate based on organic additives The only difference from Example 1 is that the sintering temperature in step (3) is 740°C.

[0030] Example 4: A method for preparing high-pressure lithium iron phosphate based on organic additives The only difference from Example 1 is that the organic additive in step (1) is citric acid.

[0031] Example 5: A method for preparing high-pressure lithium iron phosphate based on organic additives The only difference from Example 1 is that the sintering temperature in step (3) is 810°C.

[0032] Example 6: A method for preparing high-pressure lithium iron phosphate based on organic additives The only difference from Example 1 is that the sintering time in step (3) is 8 hours.

[0033] Example 7: A method for preparing high-pressure lithium iron phosphate based on organic additives The only difference from Example 1 is that the organic additive titanium citrate in step (1) is 0.8% of the mass of iron phosphate.

[0034] Example 8: A method for preparing high-pressure lithium iron phosphate based on organic additives The only difference from Example 1 is that in step (1), lithium carbonate and iron phosphate are added at a Li:Fe:P molar ratio of 1.02:1:1.04.

[0035] Comparative Example 1: The only difference between it and Example 1 is that the organic additive in step (1) is 0%.

[0036] Performance testing 1. Compaction density test: The lithium iron phosphate obtained in Examples 1-8 and Comparative Example 1 were tested using a compaction density meter. The test pressure was 3 tons, and the results are shown in Table 1.

[0037] 2. Capacity performance test: The above materials are mixed in a mass ratio of lithium iron phosphate:PVDF:conductive carbon black = 8:1:1 to form a slurry, which is then coated onto aluminum foil to form a positive electrode and a negative electrode lithium sheet to form a button cell. The specific capacity of 1C and 0.1C discharge is tested within the range of charge and discharge cutoff voltage of 2.0 to 3.75V, as shown in Table 1.

[0038] Table 1 Performance Test Results

[0039] Results analysis: As shown in Table 1, Examples 1-8 demonstrate that the compaction density of the high-pressure lithium iron phosphate prepared according to this invention can reach 2.63 g / cm³. 3The 0.1C discharge capacity reaches over 160 mAh / g, and the 1C discharge capacity reaches over 143 mAh / g, both superior to Comparative Example 1. The preparation method of this patent features a simple synthesis process and uniform mixing, enabling large-scale production on a production line.

[0040] The organic additive selected in Example 1 of this invention is preferably titanium citrate. Such organic additives, which all contain metal elements, allow these metal elements (iron, titanium, aluminum, etc.) to enter the lithium iron phosphate lattice during sintering, contributing to a stable crystal structure and acting as a dual-functional precursor for doping and coating. The titanium element in titanium citrate can selectively enter the lithium iron phosphate lattice, forming stable Ti-OP bonds, effectively opening lithium-ion migration channels and reducing the migration energy barrier; simultaneously, its organic components decompose to form a highly graphitized, uniform carbon coating layer. This in-situ synergistic effect of lattice doping and conductive coating is key to simultaneously improving ionic and electronic conductivity from the material's fundamental nature, thereby ensuring excellent rate performance and capacity utilization while achieving high solid density.

[0041] The above descriptions are merely embodiments of the present invention, and common knowledge regarding specific structures and characteristics is not elaborated upon here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the structure of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing high-pressure lithium iron phosphate based on organic additives, characterized in that, Includes the following steps: S1. A lithium source, an iron source, a phosphorus source, a carbon source, and an organic additive are mixed in pure water to obtain a mixture; wherein the organic additive is one or more of ferric citrate, titanium citrate, and aluminum citrate; the amount of the organic additive added is 0.5-5% of the mass of the iron source; S2. The mixture is wet-milled to obtain a slurry with a solid particle size D50 of 0.2 to 0.6 μm; S3. Spray dry the slurry to obtain lithium iron phosphate precursor; S4. The lithium iron phosphate precursor is sintered under an inert gas protective atmosphere to obtain a lithium iron phosphate cathode material; the sintering temperature is 740-770℃.

2. The method for preparing high-pressure lithium iron phosphate based on organic additives according to claim 1, characterized in that: In S1, the carbon source is one or more of sucrose, glucose, starch, PEG, ascorbic acid, and cellulose.

3. The method for preparing high-pressure lithium iron phosphate based on organic additives according to claim 1, characterized in that: In S1, the amount of carbon source added is 5% to 15% of the mass of the iron source.

4. The method for preparing high-pressure lithium iron phosphate based on organic additives according to claim 1, characterized in that: In S1, the phosphorus source is one or more of phosphoric acid, monoammonium phosphate, diammonium phosphate, and ferric phosphate; the iron source is one or more of ferrous oxalate, ferric phosphate, iron oxide, ferric pyrophosphate, ferrous dihydrogen phosphate, and ferrous phosphate; the lithium source is one or more of lithium carbonate and lithium hydroxide; and the elemental molar ratio of the lithium source, iron source, and phosphorus source is Li:Fe:P = 1~1.05:1:1~1.

07.

5. The method for preparing high-pressure lithium iron phosphate based on organic additives according to claim 1, characterized in that: In S1, the solid content of the mixture is 30% to 60%.

6. The method for preparing high-pressure lithium iron phosphate based on organic additives according to claim 1, characterized in that: In S4, the inert gas is one or both of argon and nitrogen.

7. The method for preparing high-pressure lithium iron phosphate based on organic additives according to claim 1, characterized in that: In S4, the sintering time is 6 to 14 hours.

8. The application of the method for preparing high-pressure lithium iron phosphate based on organic additives according to any one of claims 1-7 in the preparation of batteries.

Citation Information

Patent Citations

  • Rapid method for preparing LiFePO4 cathode material

    CN102225752B

  • A preparation method of high conductivity lithium iron phosphate material

    CN109244462A

  • Lithium iron phosphate positive electrode material and preparation method and application thereof

    CN118043999A

  • Water-soluble organic titanium compound as well as preparation method and application thereof

    CN118878575A